Implementation interventions to promote healthcare professional uptake of evidence-based opioid prescribing for adults with acute non-cancer pain - Wallis, Jason A; Langford, Aili V; O'Connor, Denise; Reeve, Emily; Ackerman, Ilana N; Haas, Romi; Docking, Sean; Cross, Amanda J; Turner, Justin; Johnston, Renea V; Gorelik, Alexandra; Cyril, Sheila; et al. (Cochrane database of systematic reviews, 2025)
This is a protocol for a Cochrane Review (intervention). The objectives are as follows: The primary objective is to assess the effects of implementation interventions aimed at improving the uptake of evidence-based opioid prescribing by healthcare prescribers for adults with acute non-cancer pain, compared with no intervention. The secondary objectives are. To explore whether the effects vary by intervention type (e.g. audit and feedback), target (e.g. healthcare prescribers), setting of implementation intervention (e.g. primary care), and type of pain (e.g. postsurgical pain). To summarise the availability and principal findings of eligible economic evaluations of the implementation interventions.